Microstructural deformation patterns of a highly orthotropic polypropylene separator of lithium-ion batteries: Mechanism, model, and theory. (May 2020) - Pan, Zhexin; Zhu, Juner; Xu, Hongyi; Sedlatschek, Tobias; Zhang, Xiaowei; Li, Wei; Gao, Tao; Xia, Yong; Wierzbicki, Tomasz
Abstract: Dry-processed polyolefin film is currently the most widely-applied type of separators for commercial lithium-ion batteries. Its porous structure could undergo large deformation during normal charging–discharging cycles, affecting the mass transfer process through the electrolyte, and during mechanical abuse loadings, leading to the direct contact between the positive and the negative electrodes and the subsequent electrical short circuit. In this study, we investigate its deformation pattern experimentally via mechanical testing with post-mortem microscopic examinations, numerically via an image-based microstructural modeling technology, and theoretically via an analytical model based on the principle of minimum energy. The developed models and theories provide high-fidelity predictions of the deformation patterns under different conditions compared with the experimental observations.